Production of polymethyl methacrylate grafted biopolymer using potassium persulfate - Qudsieh, I. Y.; Mirghani, Mohamed Elwathig Saeed; Matar, Saleh M.; Alkhatib, Maan F.; Kabbashi, Nassereldeen Ahmed (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
The production of the biodegradable poly (methyl methacrylate) (PMMA) onto sago starch biopolymer (Starch-gPMMA) was carried out using potassium persulfate (PPS) as an initiator. PMMA was grafted onto starch using PPS as an initiator under nitrogen gas atmosphere. The maximum percentage of grafting (%G) was determined to be 90%. The optimum conditions were as follows: reaction temperature: 500C, the amount of monomer: 47 m.moles, the amount of PPS: 1.82 m.moles, and reaction period: 1.5 hr. The copolymers produced were characterized by Fourier Transform Infrared Spectrophotometry (FTIR), The FTIR spectra of the copolymers clearly indicated the presence of characteristic peaks of PMMA and starch, which suggested that PMMA had been successfully grafted on the starch.